DİETLE ALINAN KURŞUNUN ERİTROSİT OSMOTİK DİRENÇ VE KAN VİSKOZİTESİNE ETKİLERİNİN ARAŞTIRILMASI - ÖZÇELİK, Derviş and TOPLAN, Selmin and DARIYERLİ, Nuran and Gülyaşar, Tevfik and DURSUN, Şefik (Cerrahpaşa Medical Journal, 2014)
Background.- In this study, the effect of lead concentration on blood viscosity and erythrocyte osmotic resistance were tried to be investigated in rats. Design.- Fourteen Wistar-Albino type female rats were picked and animals were divided into two as control and experimental groups. Nutrition's type and content of both groups was same. But lead acetate was added to the drinking water of experimental group for four weeks. At the end of fourth week, blood samples were drawn from abdominal aorta of rats. Blood viscosity and erythrocyte osmotic fragility were determined. Results.- While increase in blood lead concentration values of experimental group was detected, the osmotic resistance and blood viscosity values were found to be decreased according to the same parameters of control group. Conclusion.- Our study indicated that the intake of lead through the drinking water leads to reduce of blood viscosity and osmotic resistance of erythrocytes.